The Relationship Between Multinationality, Transfer Pricing Aggressiveness, and Tax Haven on Tax Avoidance - Christine Natalie Raka Sareng (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Indonesia's tax ratio remains below the 15 percent threshold recommended by the International Monetary Fund (IMF), reflecting a significant gap in tax revenue collection. This low ratio may indicate the presence of aggressive tax planning strategies, including tax avoidance practices, particularly among multinational enterprises. This study aims to empirically examine the relationship between multinationality, transfer pricing aggressiveness, and the use of tax havens on tax avoidance. The research focuses on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. A total of 64 companies were selected as samples through purposive sampling based on specific criteria, including the availability of relevant financial data and disclosure of international operations. The variables analyzed include the degree of multinationality, transfer pricing aggressiveness as proxied by related party transactions, and involvement with tax haven jurisdictions. The dependent variable, tax avoidance, is measured using the effective tax rate (ETR) approach. Data were processed and analyzed using multiple linear regression analysis with the aid of STATA version 17. The findings of the study reveal that multinationality and transfer pricing aggressiveness do not have a significant relationship with tax avoidance. In contrast, the use of tax haven countries is positively associated with tax avoidance, suggesting that firms utilizing tax havens are more likely to engage in practices that reduce their tax liabilities. These results have implications for tax authorities in identifying and addressing high-risk corporate behaviors related to offshore financial structures. The study contributes to the literature on international taxation by providing empirical evidence from a developing country context.